Accounting for individual differences in the response to tDCS with baseline levels of neurochemical excitability. (June 2019) - Filmer, Hannah L.; Ehrhardt, Shane E.; Bollmann, Saskia; Mattingley, Jason B.; Dux, Paul E.
Abstract: There is now considerable evidence that applying a small electrical current to the cerebral cortex can have wide ranging effects on cognition and performance, and may provide substantial benefit as a treatment for conditions such as depression. However, there is variability across subjects in the extent to which stimulation modulates behaviour, providing a challenge for the development of applications. Here, we employed an individual differences approach to test if baseline concentrations of the neurochemicals GABA and glutamate are associated with an individual's response to transcranial direct current stimulation (tDCS). Using a previously replicated response selection training paradigm, we applied tDCS to the left prefrontal cortex part-way through the learning of a six-alternative-forced-choice task. Across three sessions, subjects received anodal, cathodal, or sham stimulation. Pre-tDCS baseline measures of GABA and glutamate, acquired using magnetic resonance spectroscopy (MRS), correlated with the extent to which stimulation modulated behaviour. Specifically, relative concentrations of GABA and glutamate (used as an index of neurochemical excitability) in the prefrontal cortex were associated with the degree to which active stimulation disrupted response selection training. This work represents an important step forward in developing models to predict stimulation efficacy, and provides a unique insight into how trait-based properties of the targeted cortex interact with stimulation.